The underground workspaces questionnaire (UWSQ): Investigating public attitudes toward working in underground spaces. (15th April 2019) - Lee, Eun Hee; Luo, Chengwen; Sam, Yoke Loo; Roberts, Adam C.; Kwok, Kian Woon; Car, Josip; Soh, Chee-Kiong; Christopoulos, George I.
Abstract: Over half of the global population lives in urban areas, making the issue of space a pressing environmental factor. The development of large-scale underground complexes in (mega-)cities is a solution to healthy urban growth and many governments have already adopted the development of underground (office) workspaces (UWS). Engineering can develop such high quality spaces; yet, there is limited understanding of how the public perceives UWS. UWS are not the same as other workspaces, and thus special assessment tools are needed. Here, we present the Underground Workspaces Questionnaire (UWSQ), which measures pre-occupant attitudes towards UWS. Analysis (N > 1000) identified three factors with positive aspects associated with feeling protected, whereas confinement was independent of affective responses. Predictably, responses to the three factors correlated with claustrophobia but were independent constructs. UWSQ can help policymakers and architects understand how populations holistically respond to the idea of working in an underground office. Highlights: Many cities are adopting underground workspaces (UWS) as a promising solution for combating urban sprawl. We present the first standardized (N > 1, 000) questionnaire examining attitudes towards the prospect of working in an UWS. Statistical analyses disclosed 1 positive and 2 negative factors; factors were related to but independent of claustrophobia. The tool can help policy makers to identify, in a statistically valid way, how the public responds to UWS.